The Implementation of Child-Friendly School Management in the Learning Process - Handayani, Ery; Kusumaningsih, Widya; Sulianto, Joko (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to examine the implementation of Child-Friendly School (CFS) management in the learning process at SMP Negeri 39 Semarang. The research focuses on how planning, organizing, implementation, and supervision are carried out to ensure the fulfillment of children’s rights within classroom practices. A qualitative case study approach was employed to obtain an in-depth understanding of managerial and instructional processes. Data were collected through in-depth interviews, classroom observations, and document analysis involving the principal, vice principals, teachers, students, and parents. Data validity was ensured through source and technique triangulation, while data analysis followed the stages of reduction, display, and conclusion drawing. The findings indicate that the implementation of Child-Friendly School management in the learning process has been carried out effectively. In the planning stage, teachers are directed to design student-centered lesson plans that integrate child-friendly principles. The organizing stage shows a clear distribution of roles and responsibilities among school members, including the involvement of parents and the school committee. During implementation, teachers apply active learning strategies, positive communication, and non-violent discipline, creating a safe, inclusive, and enjoyable learning environment. In the supervision stage, regular monitoring and evaluation are conducted to ensure consistent application of child-friendly principles, although continuous monitoring and teacher capacity strengthening remain necessary. Overall, the study concludes that effective management of Child-Friendly Schools contributes positively to the creation of a humane, participatory, and rights-based learning process, supporting students’ academic and socio-emotional development.